The limit group as a Hopf algebra - Mendoza Quispe, Wilfredo (2023)
In this work we will preliminarily present the deﬁnition of H-spaces, followed by them we will study the Bockstein spectral sequence that together with the exact pairs will allow us to deﬁne the so-called limit group associated with each spectral sequence. We also review the properties of string complexes and the complex homology of an elementary string. In the last section we present the spectral Bockstein sequence for H-spaces and Hopf algebras. In this context we prove that the limit group can be expressed isomorphically as a Hopf algebra.